1983
DOI: 10.1037/h0088473
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical giving up and the reduction of sleep performance anxiety in chronic insomniacs.

Abstract: Paradoxical intention has been shownto improve sleep performance in chronic insomniacs, presumably by interrupting their overly anxious sleep efforts. Instructions to simply give up such sleep intentions-without trying to stay awake -could have a similar effect. Giving-up instructions framed as a paradoxical sleep-improvement method ("try giving up") were compared here with giving up presented as a way to improve nighttime comfort and morning restedness without any sleep improvement ("give up trying"), along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Paradoxical intention is thought to alleviate insomnia by eliminating effort to sleep, and therefore reducing sleep related performance anxiety (Ascher & Turner, 1979a). However, this proposal remains largely untested (Fogle & Dyall, 1983). Moreover, whilst outcome studies from clinical case reports and experimental studies suggest the technique can be very useful (Ascher & Turner, 1979a), some response variability has also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxical intention is thought to alleviate insomnia by eliminating effort to sleep, and therefore reducing sleep related performance anxiety (Ascher & Turner, 1979a). However, this proposal remains largely untested (Fogle & Dyall, 1983). Moreover, whilst outcome studies from clinical case reports and experimental studies suggest the technique can be very useful (Ascher & Turner, 1979a), some response variability has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…. As noted, it is assumed that paradoxical intention operates to reduce SOL by alleviating effort to sleep and obviating performance anxiety, and as outlined above, there is tentative evidence for this proposal from the insomnia (Fogle & Dyall, 1983) and clinical treatment literature's . Thus, non-responders may be unsuited to paradoxical intention due to low levels of performance anxiety and effort to…”
Section: Paradoxical Intention: Evidence Of Response Variabilitymentioning
confidence: 97%
“…Although it does not seem unreasonable to suppose that cultural variables may influence the way in which LOC moderates life stresses, only two studies thus far reported have tested for such differential moderation effects (Dyal, 1982;Dyal et αϊ., 1982). For example, if immersion in a Karma-oriented Zeitgeist fostered a "giving up" problem dissolution approach to anxiety-driven problem behaviors (Fogle & Dyal, 1983), then externality might in fact serve to reduce the stress of negative life events for Asians, whereas internality moderates life stresses for control-oriented cultures such as those of North America. For example, if immersion in a Karma-oriented Zeitgeist fostered a "giving up" problem dissolution approach to anxiety-driven problem behaviors (Fogle & Dyal, 1983), then externality might in fact serve to reduce the stress of negative life events for Asians, whereas internality moderates life stresses for control-oriented cultures such as those of North America.…”
Section: North American Minority Groupsmentioning
confidence: 99%
“…1. There is a relatively consistent series of studies on insomnia (Ascher & Efran, 1978;Ascher & Turner, 1979Fogle & Dyal, 1983;Lacks et al, 1983;Ott et al, 1983;Relingeret al, 1978;Ribordy& Denney, 1977;Turner & Ascher, 1979 which suggests that straightforward paradoxical intention using symptom prescription and a simple rationale is generally effective in reducing sleep onset latencies when compared with control procedures. However, paradoxical intention may not be as effective as stimulus control techniques (see Bootzin, 1977), and may not be particularly useful with mild degrees of insomnia.…”
Section: Assessing Paradoxical Interventionsmentioning
confidence: 96%